Quality of hospital services in 5S-KAIZEN-TQM implemented secondary level hospital: a cross-sectional study - Rouf, Md Abdur; Debnath, Sumon Chandra; Haque, Md Ekramul; Chowdhury, Zobaid Mohammad Rahat; Hasan, Dewan Md Mehedi; Zannat, Taslima; Rabby, Md Fazlay (Asian Journal of Medical and Biological Research, 2017)
This cross-sectional study was conducted with an objective to find out the quality of health care services in 5S-KAIZEN-TQM implemented two secondary level hospital in Bangladesh. The study participants were the service receiver’s whose age more than 15 years and those who were attended at 100 bedded Narsingdi General Hospital, Bangladesh. The period of the study extending from January to December 2016. Data were collected from 50 service receivers through face to face interviews using a semi-structured questionnaire. Out of 50 respondents, half (50.0%) of the service receiver was ≤ 25 years in which maximum (74.0%) were female. More than half of the respondent’s monthly income was less than 20000 taka. In this study, half (50.0%) of the respondents stated that they were waiting for 15-30 minutes, 60.0% patients stated that the doctor had concentrated to patients during treatment and more than two-third (68.0%) of them performed physical examination. A vast majority (90.0%) of the patients said that the doctor gave the explanation of prescribed drug. More than three-fourth (76.0%) of the respondents replied that they were satisfied on receiving the nursing services and rest of them (24.0%) were not satisfied. The present study findings stated that less than two-third (64.0%) of the respondents said that safety and security system was very good. On the other hand, 64.0% of the respondents were satisfied about cleanliness of the hospital and 88.0% had satisfied about ambulance service. Maximum of the respondents (88.0%) were satisfied on water and sanitation facility and more than half (54.0%) of the respondents were satisfied on electricity supplies in the hospital. In this study, majority (88.0%) of the respondents were satisfied on lab investigation facilities and 72.0% of the respondents were satisfied on drug supply and radiology and imaging services. 5S could be applied to health-care facilities regardless of locations. However, the evidence base on its applicability in such settings is limited, and further research is required in this area. Asian J. Med. Biol. Res. September 2017, 3(3): 335-340